Dolarización de Obligaciones, Fragilidad Financiera y Desempeño Macroeconómico - PROAÑO ACOSTA, CHRISTIAN (2005)
The liability dolarization, a caracteristic phenomenon of the so called emerging economies, is considerated as one of the main causes for the conexion between currency and financial crises. As many crises in the last years have demonstrated, these episodes can provoke grave effects in the macroeconomic performance of the affected economies. In this article the main causes and reasons for the liability dolarization in emerging economies are discussed and a theoretical model is presented which is able to represent some macroeconomic scenarios which can occur after the outbreak of a currency and financial crisis in the medium run.